Acute disseminated encephalomyelitis associated with enterovirus 71 - Kato, Zenichiro; Omoya, Kentaro; Orii, Kenji E.; Kondo, Naomi (Journal of Pediatric Infectious Diseases, 2006)
Acute disseminated encephalomyelitis is an immune-mediated inflammatory demyelinating disease of the central nervous system that can occur during or after infections. A 2-year-old female was hospitalized in an unconsciousness state with fever. She had suffered from 5 days of hand-foot-mouth disease until 2 days before admission. Magnetic resonance imaging disclosed high-intensity lesions at the cerebrum and cerebellum but not at the brainstem and spinal cord, confirming the diagnosis of acute disseminated encephalomyelitis. Her illness was remarkably improved after the start of steroid therapy and she could recover without any sequele. The genetic analysis of the genome sequence revealed that the isolated strain was enterovirus 71. The phylogenetic analysis with the strains obtained from fatal brainstem encephalitis suggests an association between the genotypes and the neurological virulency.
Keywords: ADEM; enterovirus 71; child